'Prototypical' proinflammatory cytokine (IL-1) in multiple sclerosis: role in pathogenesis and therapeutic targeting. (2nd January 2020) - Musella, Alessandra; Fresegna, Diego; Rizzo, Francesca Romana; Gentile, Antonietta; De Vito, Francesca; Caioli, Silvia; Guadalupi, Livia; Bruno, Antonio; Dolcetti, Ettore; Buttari, Fabio; Bullitta, Silvia; Vanni, Valentina; et al.
ABSTRACT: Introduction : It has been recognized for about 20 years that interleukin (IL)-1 signaling is implicated in Multiple Sclerosis (MS), a disabling, chronic, inflammatory and neurodegenerative disease of the central nervous system (CNS). Only recently, multifaceted roles of IL-1 emerged in MS pathophysiology as a result of both clinical and preclinical studies. Notably, drugs that directly target the IL-1 system have not been tested so far in MS. Areas covered : Recent studies in animal models, together with the development of ex vivo chimeric MS models, have disclosed a critical role for IL-1 not only at the peripheral level but also within the CNS. In the present review, we highlight the IL-1-dependent neuropathological aspects of MS, by providing an overview of the cells of the immune and CNS systems that respond to IL-1 signaling, and by emphasizing the subsequent effects on the CNS, from demyelinating processes, to synaptopathy, and excitotoxicity. Expert opinion : Drugs that act on the IL-1 system show a therapeutic potential in several autoinflammatory diseases and preclinical studies have highlighted the effects of these compounds in MS. We will discuss why anti-IL-1 therapies in MS have been neglected to date.